Management of Powdery Mildew in Beans - Qingren Wang; Shouan Zhang; Teresa Olczyk (EDIS)
Powdery mildew is one of the most commonly occurring diseases on many types of beans. Although the causal organism rarely causes extensive damage, significant yield losses were reported in Columbia County when infection occurred in dry beans prior to flowering. Accurately identifying this disease and immediately taking action for control are critical to effectively prevent spread of powdery mildew in order to reduce significant losses of yield and quality. This 4-page fact sheet was written by Qingren Wang, Shouan Zhang, and Teresa Olczyk, and published by the UF Department of Plant Pathology, June 2014.